Outstanding fundraising practice: how do nonprofits substantively increase their income?. Issue 1 (19th January 2016) - Sargeant, Adrian; Shang, Jen
Abstract : In this paper, we examine the characteristics of charities that have generated substantive increases in their fundraising income. We interviewed 25 fundraising directors and team members, from organizations experiencing rapid growth, adopting a "decoding the discipline" approach to identify how each organization had overcome key barriers to its success. We identify that fundraising leaders in these exceptional nonprofits focus particularly on matters connected to their team, organizational structures that support that team, and the development of an organization‐wide learning culture. We also find that these teams were successful because of the "systems" way in which they understood and coped with the complexities of decision making. They were exceptional in isolating the right problems and exceptional too in the processes they adopted to solve them. Copyright © 2016 John Wiley & Sons, Ltd.